A Contrastive Analysis of Elative Constructions in English and Lithuanian - Roikienė, Dalė (Kalbotyra, 2003)
The article focuses on the semantic structure and the linguistic means to realize the semantic functions of the Elative constructions in English and Lithuanian. The Elative can be defined as a starting point (Source), from which an entity (Trajector) moves or has its origin. Besides, the construction includes the route taken (Path) and the end point (Goal, Landmark). In both languages Source may denote closed and open containers, a certain environment. In addition, abstract entities can also serve as a starting point. In this case, the initial point of movement is from a place of activity. In English the semantic components are realized syntactically, in Lithuanian syntactically and morphologically.